MAINTAINING THE QUALITY OF LIGHT PETROLEUM PRODUCTS IN LONG-TERM STORAGE CONDITIONS - VOVK, YULIIA; MATVYEYEVA, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper is devoted to highlighting the relevance and necessity of a comprehensive and systematic approach to fuel quality control and the improvement of modern technologies for its storage. This is a key factor not only in maintaining the operational characteristics of light petroleum products but also in reducing their negative impact on the natural environment and ensuring the effective, rational, and safe use of existing energy resources. Based on theoretical generalizations and the results of experimental research, the paper develops practical recommendations for the long-term storage of light petroleum products. The need for implementing these recommendations in accordance with current regulatory and technical requirements, environmental standards, and production needs is substantiated. The proposed solutions aim to improve the reliability of fuel systems and reduce the risk of product quality deterioration during storage. The authors present a clear algorithm of actions to be taken in case of microbiological contamination of light petroleum products or the technological equipment used in their storage. A system of timely and effective measures for the removal of bottom water from fuel storage tanks is also proposed, which helps prevent undesirable physical and chemical changes in the product. Special attention is paid to the formulation of enterprise policy in the field of petroleum product storage, which includes the introduction of a set of organizational and technological measures. The importance of regular quarterly fuel test analyses is particularly emphasized, as they allow timely detection of microbiological contamination and help prevent its further development. The results obtained from this research can be used to update existing industry regulatory documents on petroleum product storage. In turn, this will contribute to improving environmental sustainability, energy efficiency, operational reliability, and the safety of fuel supply systems at industrial facilities.